Spatial, temporal and latitudinal components of historical fire regimes in mixed conifer forests, California. (15th December 2016) - Krasnow, Kevin D.; Fry, Danny L.; Stephens, Scott L.
Abstract: Aim: This study seeks to document and compare historical temporal and spatial components of fire regimes in two watersheds in mixed conifer forests of the western slope of the Sierra Nevada, California, USA. Location: Watersheds in the southern Sierra Nevada (Sugar Pine, 2358 ha) and north‐central Sierra Nevada (Last Chance, 3021 ha), California, USA are compared. Methods: Temporal (frequency, return interval, season) and spatial (extent, fire rotation, spatial mean fire interval) fire regime metrics were reconstructed from fire scar samples. Superposed epoch analysis (SEA) was used to examine relationships between fire occurrence and the Palmer drought severity index (PDSI) at each site. Thin plate splines were introduced as a tool for interpolating historical fire extent from dendroecological data. Point fire return intervals were compared between sites to better understand possible influences of historical Native American burning practices. Results: Differences emerged between sites in temporal and spatial fire regime metrics. The northern site had longer fire return intervals, more synchronized fire years, fewer point intervals < 4 years, longer fire rotation period and longer spatial mean fire interval. The northern site showed a significant reduction in PDSI values during fire years, whereas this climate–fire relationship in the southern site was likely decoupled by frequent Native American burning. Thin plate spline interpolation effectively reduced discontinuities at sample points compared to inverse distance weighting methods. Main conclusions: Differences in both temporal and spatial fire regime metrics between sites were likely due to interplay in latitudinal influence on climate as well as differential Native American burning practices. Reconstruction of historical fire areas via geographical interpolation of fire scar data holds great promise for spatially explicit fire frequency reconstruction. The use of thin plate spline interpolation methods has the potential to reduce the impact of 'false negatives' in dendroecological data from frequent‐fire forests.